Genetic analysis and clinical assessment of four patients with Glycogen Storage Disease Type IIIa in China - Yu Zhang; Mingming Xu; Xiaoxia Chen; Aijuan Yan; Guoyong Zhang; Zhenguo Liu; Wenjuan Qiu (BMC, 2018)
Abstract Background Glycogen Storage Disease Type III (GSD III) is a rare autosomal recessive metabolic disorder caused by AGL gene mutation. There is significant heterogeneity between the clinical manifestations and the gene mutation of AGL among different ethnic groups. However, GSD III is rarely reported in Chinese population. Case presentation In this study, we aimed to study the genetic and clinical characteristics of four patients with GSD IIIa from China, especially the neurological manifestations. Meanwhile, we conducted a literature review of GSD IIIa cases reported in Chinese population to investigate the relationship between genotype and phenotype. Conclusions Three different AGL gene mutations were identified in our patients: c.206dupA, c.1735 + 1G > T and c.2590 C>T. Moreover, progressive myopathy accompanied by elevated creatine kinase level was the main manifestation of our patients in adolescents. Our results showed that AGL c.206dupA was a novel mutation and caused severe clinical manifestations. AGL c.1735 + 1G > T might be a recurrent mutation in the Chinese population. Genetic analysis of AGL gene mutation combined with muscle magnetic resonance imaging (MRI) might provide greater benefit to the patient in diagnosing GSD IIIa, rather than an invasive diagnostic procedure of biopsy.